Lightweight high-strength ceramsite and preparation method thereof

By using lignin and nano-titanium dioxide photocatalyst to pretreat sulfonated water-based drill cuttings, the problem of treating toxic organic matter and heavy metal ions in sulfonated water-based drill cuttings was solved, and the preparation of lightweight and high-strength ceramsite and industrial solidification were achieved. Waste resource utilization.

CN119306414APending Publication Date: 2025-01-14PETROCHINA CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310848551.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-11
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The prior art is difficult to effectively treat and utilize toxic organic matter and heavy metal ions in sulfonated water-based drill cuttings, resulting in environmental pollution and waste of resources.

Method used

Lignin is used as an adsorbent and nano-titanium dioxide photocatalyst to pretreat sulfonated water-based drill cuttings. Heavy metal ions and organic pollutants are removed through adsorption and photocatalytic degradation, and decomposed at high temperatures to produce ceramsite preparation. Reducing atmospheres and gases.

Benefits of technology

It achieves the effective disposal and utilization of sulfonated water-based drill cuttings, reduces the cost of ceramsite preparation, increases the strength and density of ceramsite, meets the requirements of industry standards, and reduces environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119306414A_ABST
    Figure CN119306414A_ABST
Patent Text Reader

Abstract

The invention provides lightweight high-strength ceramsite and a preparation method thereof, and the lightweight high-strength ceramsite is prepared from the following raw materials in parts by weight: 30-45 parts of sulfonated water-based drilling cuttings, 3-9 parts of lignin, 0.3-0.9 part of a nano titanium dioxide photocatalyst, 10-25 parts of alumina tailings, 5-15 parts of red mud and 10-25 parts of fly ash. According to the lightweight high-strength ceramsite and the preparation method thereof, sulfonated water-based drilling cuttings and other industrial solid wastes are treated in a maximized, harmless and resourceful manner, and a lightweight high-strength ceramsite product is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of oil and gas exploration solid waste recycling, and in particular to a lightweight and high-strength ceramsite and a preparation method thereof. Background Art

[0002] With the call for green environmental protection and resource utilization of solid waste, sintered lightweight ceramsite has gradually developed as a new type of green building material, and is widely used in construction, roadbed, water pollution treatment and other fields due to its unique superior properties (lightweight and high strength, thermal insulation, earthquake resistance and fireproofing, sound insulation and noise reduction, etc.) and its internal honeycomb structure. At the same time, using ceramsite to replace ordinary sand and gravel aggregates in concrete products can improve thermal insulation performance and improve the deadweight of the structure. At the same time, it can save cement, steel bars and other materials to a large extent. Traditional ceramsite preparation is usually roasted with non-renewable resources such as kaolin and shale as the main raw materials, which causes environmental pollution and excessively high costs for ceramsite preparation. Therefore, finding suitable alternative raw materials is an effective way to effectively reduce the high cost of ceramsite preparation.

[0003] In recent years, with the continuous increase in energy demand, shale gas has become one of the main driving forces for the development of the new energy economy. In the process of shale gas drilling, water-based drilling fluid is used to maintain hydrostatic pressure and well wall stability and bottom cleaning, which also leads to the generation of a large amount of solid waste sulfonated water-based drill cuttings, which is a multi-phase stable colloidal suspension system industrial waste containing clay, weighting materials, various chemical treatment agents, sewage and drill cuttings.

[0004] Traditional water-based drill cuttings are usually treated by solidification landfill, deep well reinjection, and scattering. The solidification landfill method uses a solidifying agent to mix and solidify the water-based drill cuttings, and then transfers them to a landfill pool, isolates them with an impermeable membrane, and hardens the surface. This method has high processing costs, and there is also the risk of puncture, damage, and aging of the impermeable membrane, which in turn causes pollution to groundwater and soil. The deep well reinjection method uses abandoned mines (such as abandoned coal mines) to pour the abandoned water-based drill cuttings into abandoned mines. Its treatment cost is low, but it will pollute the groundwater system, damage the ecological environment, and affect human health. The scattering method directly leads to the pollution of environmental water and soil. With the increasing attention paid to environmental issues, solid waste treatment needs to be reduced, environmentally friendly, and resource-based. Therefore, it is urgent to develop new ways to synergize multiple solid wastes to treat water-based drill cuttings and prepare green building materials.

[0005] CN201610826984.8 discloses a method for preparing lightweight high-strength fly ash ceramsite, the raw materials used in the method are composed of 70-90 parts of fly ash, 0.5-4 parts of limestone, 5.5-7 parts of clay and 1-10 parts of bauxite. A disc granulator is used for balling, and the calcination temperature is controlled at 1000-1200°C. The lightweight high-strength ceramsite prepared in this way has high porosity and a water absorption rate of 30-40%. CN201310166415.1 discloses a method for producing sintered expanded lightweight ceramsite using oily sludge and a manufacturing method thereof, wherein the lightweight ceramsite is prepared using oily sludge as raw material, and the amount of oily sludge added after treatment reaches 43-58 parts, and is mixed with solid waste from the construction industry, and a large amount of calcium oxide, calcium sulfate, carboxymethyl cellulose, iron sulfide and other substances are added to the raw materials as additives, and the sintering temperature is 1050-1200°C, and the oily sludge is limited to a powder with a particle size of less than 0.25mm after drying, and the density reaches 486kg / m3, and the cylinder pressure strength reaches 3.85MPa. CN201910484421.9 discloses a high-strength lightweight ceramsite using gold tailings and vanadium-titanium-iron tailings as the main raw materials, and the raw material composition is 55-70% of gold tailings raw materials, 5-30% of vanadium-titanium-iron tailings, 3-8% of clay, 10-35% of shale, and 0.3-20% of pore-forming agent.

[0006] Since sulfonated water-based cuttings contain a large amount of toxic organic matter, there is little research in the prior art on using sulfonated water-based cuttings as the main raw material to produce ceramsite materials. At present, harmless treatment of organic pollutants and heavy metal ions in sulfonated water-based cuttings is a major problem in the resource utilization of sulfonated water-based cuttings. Summary of the invention

[0007] In order to solve the above technical problems, the purpose of the present invention is to provide a lightweight and high-strength ceramsite and a preparation method thereof, which can maximize, harmlessly and resourcefully process sulfonated water-based drill cuttings and other industrial solid wastes to obtain a lightweight and high-strength ceramsite product.

[0008] To achieve the above-mentioned purpose, the present invention provides a lightweight high-strength ceramsite. The raw materials of the lightweight high-strength ceramsite include, by weight: 30-45 parts of sulfonated water-based drill cuttings, 3-9 parts of lignin, 0.3-0.9 parts of nano titanium dioxide photocatalyst, 10-25 parts of bauxite tailings, 5-15 parts of red mud and 10-25 parts of fly ash.

[0009] The light and high-strength ceramsite of the present invention uses lignin as an adsorbent to pretreat sulfonated water-based drilling cuttings. Due to the presence of a large number of active groups in the molecular structure of lignin, it can adsorb heavy metal ions and organic pollutants contained in sulfonated water-based drilling cuttings under room temperature roasting, thereby preventing the enrichment of heavy metal ions and organic pollutants. In addition, the lignin adsorbent will decompose at high temperature (i.e., during roasting) and provide a reducing atmosphere. In the reducing atmosphere, the O 2- will fall off from the surface, thus generating oxygen vacancies on the lattice surface, making O 2- The diffusion coefficient increases, which accelerates the sintering process. At the same time, since carbon is generated after the decomposition of lignin, the carbon will decompose into gas at high temperature, which is beneficial to the preparation of lightweight expanded clay.

[0010] The present invention also uses nano titanium dioxide photocatalysts. Under normal temperature and light environment, the surface of the nano titanium dioxide photocatalyst will generate free radicals with strong oxidizing properties, and fully react with the sulfonated water-based drill cuttings organic pollutants attached to the catalyst surface, oxidizing and degrading them into environmentally harmless CO2 and H2O. Under high-temperature roasting environment, nano titanium dioxide will cause defects in the crystals inside the ceramsite, accelerate the growth of the grains, reduce the sintering temperature, and make the crystal structure more compact.

[0011] The lightweight high-strength ceramsite of the present invention uses sulfonated water-based drill cuttings as a main raw material, thereby realizing effective disposal and utilization of water-based drill cuttings; the total amount of solid waste in the raw materials accounts for 100%, the solid waste utilization rate is high, and the preparation cost is low; in addition, no flux, foaming agent, or binder needs to be added during the roasting process, thereby realizing resource utilization of industrial solid waste and reduction of production costs to the greatest extent, and finally obtaining lightweight high-strength ceramsite that meets the specification GB / T17431.1-2010 "Light Aggregates and Test Methods Thereof Part 1: Light Aggregates".

[0012] In the above-mentioned lightweight high-strength ceramsite, preferably, the raw materials also include 9-15 parts of deionized water.

[0013] In the above-mentioned lightweight high-strength ceramsite, preferably, the sulfonated water-based drill cuttings are drill cuttings produced by a water-based drilling fluid of a sulfonated system in shale gas drilling.

[0014] During the shale gas drilling process, water-based drilling fluid is used to maintain hydrostatic pressure and well wall stability and bottom cleaning. At the same time, this also leads to the generation of a large amount of solid waste sulfonated water-based drill cuttings. Sulfonated water-based drill cuttings is a multiphase stable colloidal suspension system industrial waste containing clay, weighting materials, chemical treatment agents, sewage and drill cuttings.

[0015] The main components of the sulfonated water-based drilling fluid include clay, viscosity enhancer, viscosity reducer, weighting agent, and aqueous phase. The introduction of polymers and tri-sulfonated systems (including sulfonated lignite resin SMC, sulfonated baking glue SMK, and sulfonated phenolic resin SMP) into the drilling fluid improves its resistance to high temperature and salt. The sulfonated water-based drilling fluid is in a colloidal state in water and has good solubility in organic matter, which leads to the presence of some organic pollutants and heavy metal ions. Therefore, the tri-sulfonated water-based drilling fluid has certain hazards to the ecological environment. During the drilling process, the drill bit breaks the underground rock to form debris, which is then taken out of the well by the sulfonated water-based drilling fluid. Finally, the sulfonated water-based drilling fluid and solid waste sulfonated water-based drill cuttings that can be recycled are obtained by screening and separation.

[0016] According to a specific embodiment of the present invention, preferably, the mineral composition of the lightweight high-strength ceramsite includes celsium feldspar, fayalite and kyanite.

[0017] The present invention also provides a method for preparing the above-mentioned lightweight and high-strength ceramsite, which comprises the following steps:

[0018] S1: mixing sulfonated water-based drill cuttings with lignin and nano-titanium dioxide photocatalyst, adding deionized water, and performing light irradiation reaction to obtain pretreated materials;

[0019] S2: mixing the pretreated material with bauxite tailings, red mud and fly ash, ball-milling the mixture to obtain raw material powder, and then mixing the raw material powder with water for granulation to obtain green particles;

[0020] S3: calcining the green particles and then cooling them to obtain the lightweight and high-strength ceramsite.

[0021] The present invention adopts lignin adsorption method and nano-titanium dioxide photocatalysis method to pre-treat water-based drill cuttings, adsorbs heavy metal ions in sulfonated water-based drill cuttings at room temperature, and at the same time, nano-titanium dioxide photocatalyzes and adsorbs and degrades organic pollutants in sulfonated water-based rock cuttings under light conditions; the lignin adsorbent decomposes under high-temperature roasting, and its decomposition product can be used as a reducing agent and foaming agent, and nano-titanium dioxide decomposes under high-temperature roasting to produce TiO2, which can also promote the growth of ceramsite crystals and improve the performance of ceramsite. The present invention successfully solves the overflow of pollutants in sulfonated water-based rock cuttings by using room-temperature pretreatment technology and high-temperature vitreous solidification technology.

[0022] In addition, the present invention also combines the coordinated treatment of various industrial solid wastes, refines the raw materials through raw material grinding and improves the potential activity, and uses the combined template method to prepare green spheres to ensure that the green spheres have uniform quality and high sphericity; finally, through raw material ratio, mineral composition design, sulfonated water-based drill cuttings pretreatment, green sphere preparation, gradient sintering and step-by-step cooling, a lightweight and high-strength expanded clay with celsium feldspar, kyanite and fayalite as the main crystal phases and meeting the industry standard requirements is fired.

[0023] In the above-mentioned method for preparing lightweight high-strength ceramsite, preferably, the method for preparing lightweight high-strength ceramsite further comprises: preliminarily crushing and drying the sulfonated water-based drill cuttings, bauxite tailings and red mud, respectively.

[0024] In the above method for preparing lightweight high-strength ceramsite, preferably, the light source in the light irradiation reaction is a 30-40W ultraviolet lamp, the light wavelength is 360-380nm, the test environment temperature is 23-28°C, and the reaction time is 10-30h. The light wavelength is more preferably 365nm.

[0025] In the above-mentioned method for preparing lightweight and high-strength ceramsite, preferably, S1 also includes filtering, drying and crushing the light irradiation reaction product in sequence, and the powder obtained by crushing is the pretreated material.

[0026] In the above-mentioned method for preparing lightweight and high-strength ceramsite, preferably, the ball milling is wet ball milling.

[0027] In the above-mentioned method for preparing lightweight high-strength ceramsite, preferably, the mass ratio of grinding balls, mixed materials and water in wet ball milling is 3-5:0.5-2:0.5-2; and the ball milling time is 1-4h.

[0028] In the above-mentioned method for preparing lightweight and high-strength ceramsite, preferably, S2 also includes filtering and drying the slurry after ball milling, and then grinding, dispersing and sieving the dried solid to obtain the raw material powder.

[0029] In the above-mentioned method for preparing lightweight and high-strength ceramsite, preferably, the sieving is performed through a 60-90 mesh sieve.

[0030] In the above-mentioned method for preparing lightweight and high-strength ceramsite, preferably, the diameter of the green particles is 4-7 mm.

[0031] In the above-mentioned method for preparing lightweight and high-strength ceramsite, preferably, the granulation adopts a combined template method.

[0032] In the above-mentioned method for preparing lightweight and high-strength ceramsite, preferably, S2 further comprises: polishing the green embryo particles with raw material powder.

[0033] In the above method for preparing lightweight high-strength ceramsite, preferably, S2 further comprises drying the polished green granules at a drying temperature of 100-110°C.

[0034] The present invention adopts a combined template method for granulation. The specific experimental method of the combined template method is as follows: (1) the ground mixed powder is mixed with an appropriate amount of water and kneaded into a dough state, and then the kneaded raw materials are divided into blocks and placed in a granulator to extrude the raw materials into strips, and then the strips are placed on a granulation plate, and the two plates are pressed together and rolled to prepare green particles with a specified particle size; (2) the green particles are placed in a sugar coating machine and continue to roll for 2-5 minutes (too long a time will cause the already formed green particles to deform during the rolling process), and a small amount of dry powder is added to make the powder green bodies bond to each other, thereby improving the green strength and sphericity of the green body, and preparing a green body with a certain strength.

[0035] The present invention utilizes template pressing to ensure that the green ball has uniform quality, and then puts it into a sugar coating machine for rolling and adding mixed powder for polishing, thereby ensuring that the green ball has excellent sphericity and realizing controllable green particle size.

[0036] In the above-mentioned method for preparing lightweight high-strength ceramsite, preferably, in S3, the calcination is carried out by a gradient sintering method;

[0037] The first gradient calcination temperature is 300-500° C., and the time is 10-30 min; the second gradient calcination temperature is 1220-1280° C., and the time is 10-30 min.

[0038] In the above-mentioned method for preparing lightweight high-strength ceramsite, preferably, during calcination, the heating rate to the first gradient calcination temperature is 5-20°C / min.

[0039] In the above-mentioned method for preparing lightweight and high-strength ceramsite, preferably, the heating rate to the second gradient roasting temperature is 5-20°C / min, wherein before the heating to 1200°C, the heating rate is 10-20°C / min, and after the heating to 1200°C, the heating rate is 5-10°C / min.

[0040] In the above-mentioned method for preparing lightweight and high-strength ceramsite, preferably, the cooling in S3 adopts a staged cooling method; when the temperature is higher than 1100°C, the cooling rate is 2-5°C / min, and when the temperature is lower than 1100°C, it is cooled with the furnace.

[0041] The present invention adopts a staged cooling method. In the high temperature stage, the viscosity of the high temperature liquid phase will increase sharply as the temperature decreases. The use of thermal insulation and slow cooling is conducive to maintaining the viscosity of the high temperature liquid phase inside the ceramsite, thereby maintaining a good porosity inside it. At the same time, thermal insulation and slow cooling can increase the crystallinity of the crystal phase inside the ceramsite, reduce the formation of the glass phase, and is conducive to the development of the crystal structure inside the ceramsite.

[0042] According to a specific embodiment of the present invention, preferably, Figure 1 As shown, the preparation method of the lightweight high-strength ceramsite comprises the following steps:

[0043] a. Primary crushing: Use a jaw crusher to crush the dried sulfonated water-based drill cuttings, bauxite tailings and red mud to less than 1 mm, and put them into a blast drying oven (105±5℃) to dry to constant weight;

[0044] b. Pretreatment: adding lignin and nano-titanium dioxide photocatalyst to the crushed sulfonated water-based drill cuttings powder obtained in step a, fully mixing, adding deionized water, and then pouring into a metal plate for sufficient standing and light reaction, filtering and drying the treated sulfonated water-based drill cuttings mixture to obtain a dried filter cake, and then crushing the drill cuttings filter cake into powder using a crusher to obtain a pretreated material;

[0045] c. Grinding: After bauxite tailings, red mud and fly ash are weighed according to the designed proportion, they are added into a drum ball mill together with the pretreated materials obtained in step b for mixed wet grinding. The mass ratio of corundum balls: mixed materials: water in the ball mill is 3-5:0.5-2:0.5-2. The ground slurry is allowed to stand, and after filtering off the supernatant, it is placed in a blast drying oven (105±5°C) and dried to constant weight. Finally, a fast grinder is used for grinding and dispersion. The mixed powder is sieved with a 60-90 mesh sieve to obtain raw material powder.

[0046] d. Granulation: the raw material powder obtained in step c is mixed with pre-weighed water, and granulated by a combined template method to obtain green embryo granules with a diameter of 5-6 mm. After granulation, the green embryo granules are placed in a sugar coater for polishing, and a trace amount of raw material powder is added during the process. After granulation, the green embryo granules are placed in a forced air drying oven (105±5° C.) for drying to constant weight to obtain dry green embryo granules;

[0047] e. Calcination: The dried green particles obtained in step d are placed in a resistance furnace for calcination by a gradient sintering method. The calcination schedule is as follows: the temperature is raised from room temperature to 300-500°C at a rate of 5-20°C / min, kept at that temperature for 10-30min, and then raised to 1220-1280°C at a rate of 5-20°C / min (the temperature is ≤1200°C at a rate of 10-20°C / min, and the temperature is ≥1200°C at a rate of 5-10°C / min), and kept at that temperature for 10-30min;

[0048] f. Cooling: The high-strength and light-weight ceramsite obtained after calcination is cooled by a step-by-step cooling method. The cooling procedure is as follows: when the temperature is ≥1100°C, the cooling rate is 2-5°C / min. When the temperature is <1100°C, the ceramsite is cooled with the furnace to obtain the light-weight and high-strength ceramsite.

[0049] The technical solution provided by the present invention has the following beneficial effects:

[0050] (1) The present invention uses lignin adsorption method and nano-titanium dioxide photocatalysis method to pre-treat sulfonated water-based drill cuttings, adsorbs heavy metal ions in sulfonated water-based drill cuttings at room temperature, prevents the enrichment of heavy metal ion pollutants, and at the same time, the nano-titanium dioxide photocatalyst completes the catalytic degradation of organic pollutants. The decomposition products of lignin adsorbent at high temperature can be used as reducing agent and foaming agent, which is beneficial to the preparation of lightweight ceramsite; the added nano-titanium dioxide can promote the growth of ceramsite crystals at high temperature, increase the formation of ceramsite crystals and increase the matrix strength, and has double enhancement and clear material and technological innovation. Finally, conventional industrial solids such as waste fly ash, bauxite tailings and red mud are used, and the batching technology is carried out for the mineral components of sulfonated water-based drill cuttings, and finally the preparation of all-solid waste-based sintered lightweight high-strength ceramsite is realized. No other flux, binder, or foaming agent is added in the process, and the resource utilization of industrial solid waste and the reduction of production costs are realized to the greatest extent.

[0051] (2) The lightweight high-strength ceramsite of the present invention can be mixed with water-based drill cuttings in an amount of up to 30%-45%. The lightweight high-strength ceramsite prepared by the water-based drill cuttings has the characteristics of controllable particle size, low particle shape coefficient, low water absorption rate, light weight and high strength. The performance indicators meet the requirements of lightweight high-strength ceramsite of density grade 900 in the standard GB / T17431.1-2010 "Light aggregate and its test method Part 1: Light aggregate". BRIEF DESCRIPTION OF THE DRAWINGS

[0052] Figure 1 The present invention is a process flow chart for preparing the lightweight and high-strength ceramsite;

[0053] Figure 2a This is a finished product picture of the lightweight and high-strength ceramsite of Example 1;

[0054] Figure 2b This is a picture of the pore cross-section structure of the lightweight high-strength ceramsite of Example 1;

[0055] Figure 3 It is the XRD analysis diagram of the lightweight and high-strength ceramsite of Examples 1-5. DETAILED DESCRIPTION

[0056] In order to have a clearer understanding of the technical features, purposes and beneficial effects of the present invention, the technical solution of the present invention is now described in detail below, but it should not be construed as limiting the applicable scope of the present invention.

[0057] Example 1

[0058] This embodiment provides a method for preparing light and high-strength ceramsite. Figure 1 As shown, the details are as follows:

[0059] 1. Raw materials

[0060] Measured by weight in dry state, the raw materials used in this embodiment include: 37.5 parts of sulfonated water-based drill cuttings powder, 6 parts of lignin, 0.6 parts of nano-titanium dioxide photocatalyst, 15.5 parts of bauxite tailings, 14 parts of red mud, 15 parts of fly ash, 10 parts of deionized water, and 18 parts of water.

[0061] 2. Preparation steps

[0062] a. Primary crushing: Use a jaw crusher to crush the dried sulfonated water-based drill cuttings, bauxite tailings and red mud to less than 1 mm, and put them into a blast drying oven (105±5℃) to dry to constant weight;

[0063] b. Pretreatment: adding lignin and nano-titanium dioxide photocatalyst to the crushed sulfonated water-based drill cuttings powder obtained in step a, fully mixing, adding deionized water, pouring into a metal plate for sufficient standing, and irradiating it with a 32W (λ=365nm) ultraviolet lamp at 25°C for 24 hours, filtering and drying the treated sulfonated water-based drill cuttings mixture to obtain a dried filter cake, and then crushing the drill cuttings filter cake into powder using a crusher to obtain a pretreated material;

[0064] c. Grinding: After weighing bauxite tailings, red mud and fly ash according to the designed proportion, add them together with the pretreated materials obtained in step b into a drum ball mill and mix and wet grind for 1 hour. The mass ratio of corundum balls: mixed materials: water in the ball mill is 4:1:1. The ground slurry is allowed to stand for 3 hours, and after filtering off the supernatant, it is placed in a blast drying oven (105±5℃) and dried to constant weight. Finally, a fast grinder is used for grinding and dispersion. The mixed powder is sieved with a 60-mesh sieve to obtain raw material powder.

[0065] d. Granulation: the raw material powder obtained in step c is mixed with pre-weighed water, and granulated by a combined template method to obtain green embryo granules with a diameter of 5-6 mm. After granulation, the green embryo granules are placed in a sugar coater for polishing, and a trace amount of raw material powder is added during the process. After granulation, the green embryo granules are placed in a forced air drying oven (105±5° C.) for drying to constant weight to obtain dry green embryo granules;

[0066] e. Calcination: The dried green particles obtained in step d are placed in a resistance furnace for calcination, using a gradient sintering method, and the sintering system is: from room temperature to 400°C at a rate of 10°C / min, keep warm for 20 minutes, and then increase the temperature to a sintering temperature of 1260°C at a certain rate (when the temperature is ≤1200°C, the heating rate is 10°C / min, when the temperature is ≥1200°C, the heating rate is 5°C / min), and keep warm for 20 minutes;

[0067] f. Cooling: The high-strength and light-weight ceramsite obtained after calcination is cooled by a step-by-step cooling method. The cooling procedure is as follows: when the temperature is ≥1100°C, the cooling rate is 2°C / min. When the temperature is <1100°C, the ceramsite is cooled with the furnace to obtain the light-weight and high-strength ceramsite.

[0068] Figure 2a This is a finished product picture of the lightweight and high-strength ceramsite of this embodiment. Figure 2b This is a picture of the pore cross-section structure of the lightweight and high-strength ceramsite of this embodiment.

[0069] Example 2

[0070] This embodiment provides a method for preparing lightweight and high-strength ceramsite, which is as follows:

[0071] 1. Raw materials

[0072] Measured by weight in dry state, the raw materials used in this embodiment include: 35 parts of water-based drill cuttings, 5 parts of lignin, 0.5 parts of nano-titanium dioxide photocatalyst, 24 parts of bauxite tailings, 12 parts of red mud, 13 parts of fly ash, 9 parts of deionized water, and 16 parts of water.

[0073] 2. Preparation steps

[0074] The preparation steps are the same as those in Example 1, except that the sintering temperature in step e is 1300°C.

[0075] Example 3

[0076] This embodiment provides a method for preparing lightweight and high-strength ceramsite, which is as follows:

[0077] 1. Raw materials

[0078] Measured by weight in dry state, the raw materials used in this embodiment include: 42 parts of sulfonated water-based drill cuttings, 8 parts of lignin, 0.8 parts of nano-titanium dioxide photocatalyst, 19 parts of bauxite tailings, 8 parts of red mud, 12 parts of fly ash, 12 parts of deionized water, and 19 parts of water.

[0079] 2. Preparation steps

[0080] The preparation steps are the same as those in Example 1, except that the sintering temperature in step e is 1250°C.

[0081] Example 4

[0082] This embodiment provides a method for preparing lightweight and high-strength ceramsite, which is as follows:

[0083] 1. Raw materials

[0084] Measured by weight in dry state, the raw materials used in this embodiment include: 40 parts of water-based drill cuttings, 7.5 parts of lignin, 0.8 parts of nano-titanium dioxide photocatalyst, 12 parts of bauxite tailings, 8 parts of red mud, 12 parts of fly ash, 15 parts of deionized water, and 17 parts of water.

[0085] 2. Preparation steps

[0086] The preparation steps are the same as those in Example 1, except that the sintering temperature in step e is 1220°C.

[0087] Example 5

[0088] This embodiment provides a method for preparing lightweight and high-strength ceramsite, which is as follows:

[0089] 1. Raw materials

[0090] Measured by weight in dry state, the raw materials used in this embodiment include: 45 parts of water-based drill cuttings, 9 parts of lignin, 0.9 parts of nano-titanium dioxide photocatalyst, 10 parts of bauxite tailings, 5 parts of red mud, 19 parts of fly ash, 15 parts of deionized water, and 18 parts of water.

[0091] 2. Preparation steps

[0092] The preparation steps are the same as those in Example 1, except that the sintering temperature in step e is 1220°C.

[0093] Figure 3 The XRD analysis diagram of the lightweight high-strength ceramsite prepared in Examples 1-5 is shown in FIG. Figure 3 It can be seen that the mineral composition of the lightweight and high-strength ceramsite prepared by the present invention includes celsium feldspar, fayalite and kyanite.

[0094] Comparative Example 1

[0095] This comparative example provides a method for preparing ceramsite, which is the same as the preparation method of Example 5, except that the raw materials used in this comparative example do not contain lignin and nano-titanium dioxide photocatalyst.

[0096] Referring to GB / T17431.2-2010 "Lightweight aggregate and its test methods Part 2: Lightweight aggregate test methods", the cylinder compressive strength, bulk density, water absorption rate and particle shape coefficient of the lightweight high-strength ceramsite prepared in the above embodiment were tested, and the test results are shown in Table 1.

[0097] Table 1 Technical indicators of lightweight high-strength ceramsite (900 density grade)

[0098]

[0099] As shown in Table 1, the cylinder pressure strength, bulk density and water absorption rate of the lightweight high-strength ceramsite prepared by the present invention all meet the standards for lightweight high-strength ceramsite with a density grade of 900. However, the cylinder pressure strength of the ceramsite prepared in Comparative Example 1, in which no lignin adsorbent and nano-titanium dioxide photocatalyst were added, was relatively low.

[0100] The present invention also uses HJ 557-2010 "Solid Waste Leaching Toxicity Leaching Method-Horizontal Oscillation Method" to measure the metal ion leaching concentration of the ceramsite prepared in the above embodiment and comparative example, and the test results are shown in Table 2.

[0101] Table 2 Environmental indicators of lightweight high-strength ceramsite

[0102]

[0103]

[0104] Note: ND means not detected.

[0105] According to the results shown in Table 2, the light and high-strength ceramsite prepared by the present invention meets the requirements of GB 5985.3-2007 "Identification Standard for Hazardous Waste - Identification of Leaching Toxicity". Comparison of Example 5 and Comparative Example 1 shows that the addition of lignin and nano-titanium dioxide photocatalyst effectively reduces the components of pollutants in ceramsite.

Claims

1. A light high-strength ceramsite, wherein the raw materials of the light high-strength ceramsite include, by weight: 30-45 parts of sulfonated water-based drill cuttings, 3-9 parts of lignin, 0.3-0.9 parts of nano titanium dioxide photocatalyst, 10-25 parts of bauxite tailings, 5-15 parts of red mud and 10-25 parts of fly ash.

2. The lightweight high-strength ceramsite according to claim 1, wherein: The raw materials of the lightweight high-strength ceramsite also include 9-15 parts of deionized water.

3. The lightweight and high-strength ceramsite according to claim 1, wherein: The sulfonated water-based drill cuttings are drill cuttings produced by a water-based drilling fluid of a sulfonated system during shale gas drilling.

4. The lightweight high-strength ceramsite according to any one of claims 1 to 3, wherein: The mineral composition of the lightweight high-strength ceramsite includes balsamite, fayalite and kyanite.

5. A method for preparing the lightweight and high-strength ceramsite according to any one of claims 1 to 4, comprising the following steps: S1: mixing sulfonated water-based drill cuttings with lignin and nano-titanium dioxide photocatalyst, adding deionized water, and performing light irradiation reaction to obtain pretreated materials; S2: mixing the pretreated material with bauxite tailings, red mud and fly ash, ball-milling the mixture to obtain raw material powder, and then mixing the raw material powder with water for granulation to obtain green particles; S3: calcining the green particles and then cooling them to obtain the lightweight and high-strength ceramsite.

6. The method for preparing the lightweight and high-strength ceramsite according to claim 5, wherein: The method for preparing the lightweight high-strength ceramsite further comprises: preliminarily crushing and drying the sulfonated water-based drill cuttings, bauxite tailings and red mud.

7. The method for preparing the lightweight and high-strength ceramsite according to claim 5, wherein: In the light irradiation reaction, the light source is a 30-40W ultraviolet lamp, the light wavelength is 360-380nm, the test environment temperature is 23-28°C, and the light irradiation time is 10-30h.

8. The method for preparing light and high-strength ceramsite according to claim 5, wherein: S1 also includes filtering, drying and crushing the light irradiation reaction product in sequence, and the powder obtained by crushing is the pre-treated material.

9. The method for preparing light and high-strength ceramsite according to claim 5, wherein: The ball milling adopts wet ball milling; Preferably, the mass ratio of grinding balls, mixed materials and water in wet ball milling is 3-5:0.5-2:0.5-2, and the ball milling time is 1-4h.

10. The method for preparing light and high-strength ceramsite according to claim 5, wherein: S2 also includes filtering and drying the ball-milled slurry, and then grinding, dispersing and sieving the dried solid to obtain the raw material powder.

11. The method for preparing light and high-strength ceramsite according to claim 10, wherein: When sieving, pass through a 60-90 mesh sieve.

12. The method for preparing light and high-strength ceramsite according to claim 5, wherein: The diameter of the green particles is 4-7 mm.

13. The method for preparing light and high-strength ceramsite according to claim 5, wherein: S2 also includes: polishing the green embryo particles using raw material powder; Preferably, S2 further comprises drying the polished green embryo particles at a drying temperature of 100-110°C.

14. The method for preparing light and high-strength ceramsite according to claim 5, wherein: In S3, the calcination adopts a gradient sintering method; the first gradient calcination temperature is 300-500°C, and the time is 10-30min; the second gradient calcination temperature is 1220-1280°C, and the time is 10-30min.

15. The method for preparing light and high-strength ceramsite according to claim 14, wherein: During calcination, the temperature is increased to the first gradient calcination temperature at a rate of 5-20° C. / min.

16. The method for preparing light and high-strength ceramsite according to claim 14, wherein: The heating rate to the second gradient calcination temperature is 5-20°C / min, wherein before the heating reaches 1200°C, the heating rate is 10-20°C / min, and after the heating reaches 1200°C, the heating rate is 5-10°C / min.

17. The method for preparing light and high-strength ceramsite according to claim 5, wherein: The cooling described in S3 adopts a staged cooling method; when the temperature is higher than 1100°C, the cooling rate is 2-5°C / min, and when the temperature is lower than 1100°C, it is cooled along with the furnace.

Citation Information

Patent Citations

  • Sintering expansion type light ceramsite produced by using oily sludge and manufacture method of sintering expansion type light ceramsite

    CN103241970A

  • Preparation method of lightweight high-strength fly ash ceramsite

    CN106396634B

  • High-strength lightweight ceramic granules taking gold tailings and vanadium-titanium-iron tailings as main raw materials

    CN110105081A